Eu não troco a mata por lugar nenhum”: percepções sobre as mudanças de um bairro rural de São José de Ribamar - Carneiro, Alessânia Silva de Lucena (2021)
This work aims to show a reflection on the modernization and urbanization process in Bairro Mata, closely related to the decline of family farming as an economic activity. The place of my research is Bairro Mata, located in a rural area near the capital São Luís and the object of study are local family farmers. I carried out an ethnography, where I described the neighborhood, the Matenses and the interaction between them. As a matense and author, I sought reflections on my insertion in the field and exposed the pros and cons of my academic and social position within the neighborhood. This research had the collaboration of active and retired farmers from Mata, in addition to their families. I was able to access some different points of view about the practice of local family farming, about the neighborhood's urbanization process, I accessed information, opinions about family farming and about education as a tool for social mobility and financial prosperity in both cases. Through the various speeches cited throughout this work, different perceptions were present and thus I was able to unveil new points of view that were previously hidden for not knowing them. Through life stories that they exposed to me, I tried to expose reflections on such environmental, economic and social transformations, relating them to family farming.